Are burn centers in German-speaking countries prepared to respond to a burn disaster?: survey-based study - Shamsi, Mustafa al-; Fuchs, Paul Christian; Grigutsch, Daniel; Horter, Johannes; Seyhan, Harun; Koenigs, Ingo; Siebdrath, Julian; Schiefer, Jennifer Lynn (Burns, 2020)
Burn disasters present a challenge not only to burn centers but the entire healthcare system. Most burn centers worldwide are unprepared to deal with a burn disaster as it is an uncommon event. We investigated the status of burn center preparedness in German-speaking countries to respond to a burn disaster. Self-administered survey questionnaires were sent to the directors of burn centers; the questions of survey used before in a similar way in Belgium were translated into German language. Of the 46 questioned burn centers, 32 (78%) responded, including all of the German adult burn centers. A clear difference in the preparation status of the burn centers in the three countries was observed due to geopolitical factors such as decentralized healthcare systems. However, the healthcare system is generally well-prepared concerning command, transfer, and capacity to provide sustained supplies to handle a massive influx of patients. Nevertheless, there are some gaps in the areas of planning and preparation, funding for disaster activities, and regular training of staff for burn disasters. We call for a unified burn disaster plan and increased cooperation between burn centers and civil defense regarding communication and training. We strongly recommend the implementation of a special disaster fund and telemedicine in disaster management to circumvent shortages in burn staff.